Interaction between walkability and fine particulate matter on ischemic heart disease: A prospective cohort study in China - Jiayun Zhang; Peng Shen; Yixing Wang; Zihan Li; Lisha Xu; Jie Qiu; Jingjing Hu; Zongming Yang; Yonghao Wu; Zhanghang Zhu; Hongbo Lin; Zhiqin Jiang; et al. (Ecotoxicology and Environmental Safety)
Background: Previous studies have suggested that neighborhoods characterized by higher walkability are related to a reduced risk of ischemic heart disease (IHD), whereas exposure to PM2.5 is positively associated with risk of IHD. Nevertheless, their joint impact on IHD warrants further investigation. Methods: This prospective cohort study was performed in Yinzhou, Ningbo, China, comprising 47,516 participants. Individual-level walkability and PM2.5 were evaluated using a commercial walkability database and a land use regression (LUR) model, respectively. Hazard ratios (HRs) and 95 % confidence intervals (95 % CIs) were calculated using two Cox proportional hazards models: one based on two-year average PM2.5 levels prior to baseline, and the other incorporating time-varying PM2.5 assessed on a monthly scale. Dose-response relationships were explored using restricted cubic spline (RCS) functions. Interactions on both additive and multiplicative scales were assessed via relative excess risk due to interaction (RERI) and likelihood-ratio tests. Joint effects were explored and visualized using a 3D wireframe plot. Results: Over a median follow-up of 5.14 years, 1735 incident cases of IHD were identified. Adjusted HRs (95 % CIs) were 1.56 (1.34–1.81) per 10 μg/m3 increase in PM2.5 and 0.96 (0.94–0.98) per 10-unit increase in walkability, with both exposures exhibiting non-linear dose-response relationships. Walkability and PM2.5 were positively correlated (rs = 0.12, P < 0.001), and a multiplicative interaction was detected (Pinteraction = 0.019). Conclusion: Walkability was inversely associated with risk of IHD, whereas exposure to PM2.5 was positively associated with IHD. Notably, the pernicious effects of PM2.5 could be attenuated in areas with higher levels of walkability. Our findings underscore the significance of walkable urban design, air quality improvement, as preventive strategies for IHD.